PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN INFRASTRUKTUR JALAN MELALUI PNPM-PPIP DI DESA MUNTE KECAMATAN TUMPAAN KABUPATEN MINAHASA SELATAN - Bryan Repi; Oktavianu Porajouw (Sam Ratulangi University, 2015)
This study aims to measure the level of public participation in the development of road infrastructure in the village plantations Munte through PNPM - PPIP . Data collection was conducted from July 2014 - February 2015. Data collection was conducted from July 2014 - February 2015. The data is in the form of primary data through a list of questions or questionnaires , and secondary data is data obtained from government Munte village , as well as scientific papers related to the study . , previous literature or from the internet . The analysis technique used in this study is a descriptive analysis techniques that will be qualitative and quantitative results of this study are presented in tabular form . The results showed that the level of participation in middle category . In the planning stages of the majority of respondents are less active in participating by reason of busy work . Stages of implementation of the most respondents are not actively participating in the grounds committee perdeasaan infrastructure development program is not consistent with the results of the meeting or the decisions taken in the planning stage different from its implementation . While pemelihraan stage only 1 respondent who is not active in this stage by reason of busy work and the rest are in the active and less active , this is because the respondents have felt the results of the development so that the respondents or the public want to be involved in this stage.